High-sensitive C-Reactive Protein as a Marker for Inflammation in Irritable Bowel Syndrome. Issue 3 (March 2016) - Hod, Keren; Ringel-Kulka, Tamar; Martin, Christopher F.; Maharshak, Nitsan; Ringel, Yehuda
Abstract : Background: Recent studies demonstrated low-grade inflammation in patients with irritable bowel syndrome (IBS). However, these studies have been relatively small and do not enable examination of this factor in different subtypes of IBS and the possibility of confounding effects of comorbidities that may be associated with inflammatory responses. Goals: To investigate the association between high-sensitive C-reactive protein (hs-CRP) and the diagnosis of IBS, IBS subtypes, symptoms' severity, and IBS-associated comorbidities. Study: This cross-sectional study uses data from a large matched case-control study of IBS subjects and healthy controls (HC). hs-CRP levels were measured in all subjects. IBS diagnosis was determined by Rome III criteria, negative screening blood tests, and normal colonoscopy. Subjects were evaluated for IBS severity and associated pain and psychological comorbidities. Results: A total of 242 IBS patients and 244 HC were studied. Median hs-CRP levels in the IBS group were significantly higher than in HC (1.80; interquartile range, 0.7 to 4.04 mg/L vs. 1.20, interquartile range, 0.5 to 2.97 mg/L respectively, P <0.006). Levels were highest in IBS-D patients with greater disease severity. Hs-CRP levels mildly correlated with symptoms severity ( r =0.169, P =0.009); this correlation was stronger for the IBS-D patients ( r =0.27, P =0.006). IBS was a significant independent predictor ( P =0.025) for higher hs-CRP levels, whereas other pain and psychological comorbidities were not. Conclusions: Given these observations of cross-sectional differences in hs-CRP between IBS subtypes and severity, independent of pain and comorbidities, more research is needed to explore a possible role of low-grade inflammation in the pathogenesis and/or clinical presentation of IBS.